Field and simulated rutting behavior of hot mix and warm mix asphalt overlays. (30th December 2020) - Alimohammadi, Hossein; Zheng, Junxing; Buss, Ashley; Schaefer, Vernon R.; Williams, Christopher; Zheng, Guangfan
Highlights: Converting laboratory dynamic modulus tests to Prony Series as inputs to Abaqus. Time-depending mechanical behavior by finite element viscoelastic simulations. Empirical evaluation of simulations to predict long term performance of asphalt. Extensive field measurements for validating simulation methodologies. Abstract: Research implementing new pavement technologies often focuses on material characterization; however, expanding the research to study and validate how new technologies influence pavement design is needed for continual improvement. Numerical analysis approaches use laboratory mixture data to predict field performance. This study compares predicted rutting by MEPDG design, estimated rutting from Finite Element (FE) simulations, and actual rutting performance in the field. Ten years ago, warm mix asphalt research was underway to measure the effect of warm mix asphalt (WMA) additives and lower production temperatures on performance. WMA benefits include reduced mixing/compaction temperatures, reduced fuel consumption, and improved compatibility. In 2009, three asphalt overlay projects were constructed in Iowa using both hot mix asphalt (HMA), and WMA mixes to compare their performance. A series of dynamic modulus tests were conducted to determine dynamic modulus and phase angles of HMA and WMA mixtures. The dynamic modulus results were used to develop FE viscoelastic simulations to predict the rutting of HMA/WMA pavement sections. Iowa's pavement management system provided field rutting of WMA/HMA sections. Also, pavement sections were evaluated using mixture input parameters in the Mechanistic-Empirical Pavement Design Guide (MEPDG). The results showed MEPDG based on linear elastic theories might overestimate the rutting of asphalt pavements, especially overlays placed on Jointed Plain Concrete Pavement (JPCP). In contrast, the FEM based on viscoelastic theories more accurately predicted the rutting of pavements. Calibration coefficients are proposed by this study, which may be useful for design engineers and industrial applications to correct and modify MEPDG overlay design thicknesses for HMA/WMA mixes placed on HMA and JPCP surfaces.